Noninvasive Measurement of Sciatic Nerve Stiffness in Patients With Chronic Low Back Related Leg Pain Using Shear Wave Elastography. (6th May 2018) - Neto, Tiago; Freitas, Sandro R.; Andrade, Ricardo J.; Vaz, João R.; Mendes, Bruno; Firmino, Telmo; Bruno, Paula M.; Nordez, Antoine; Oliveira, Raúl
Abstract : Objectives: The purpose of this study was to determine whether sciatic nerve stiffness is altered in people with chronic low back–related leg pain by using shear wave elastography. Methods: In this cross‐sectional study, the sciatic nerve shear wave velocity (ie, an index of stiffness) was measured in both legs of 16 participants (8 with unilateral low back–related leg pain and 8 healthy controls). Sciatic stiffness was measured during a passive ankle dorsiflexion motion performed at 2°/s in an isokinetic dynamometer. The ankle range of motion and passive torque, as well as muscle activity, were also measured. Results: In people with low back–related leg pain, the affected limb showed higher sciatic nerve stiffness compared to the unaffected limb (+11.3%; P  = .05). However, no differences were observed between the unaffected limb of people with low back–related leg pain and the healthy controls ( P  = .34). Conclusions: People with chronic low back–related leg pain have interlimb differences in sciatic nerve stiffness, as measured by a safe and noninvasive method: shear wave elastography. The changes found may be related to alterations in nerve mechanical properties, which should be confirmed by future investigations.